Grazing alters net ecosystem C fluxes and the global warming potential of a subtropical pasture. Issue 2 (27th February 2018) - Gomez‐Casanovas, Nuria; DeLucia, Nicholas J.; Bernacchi, Carl J.; Boughton, Elizabeth H.; Sparks, Jed P.; Chamberlain, Samuel D.; DeLucia, Evan H.
Abstract: The impact of grazing on C fluxes from pastures in subtropical and tropical regions and on the environment is uncertain, although these systems account for a substantial portion of global C storage. We investigated how cattle grazing influences net ecosystem CO2 and CH4 exchange in subtropical pastures using the eddy covariance technique. Measurements were made over several wet‐dry seasonal cycles in a grazed pasture, and in an adjacent pasture during the first three years of grazer exclusion. Grazing increased soil wetness but did not affect soil temperature. By removing aboveground biomass, grazing decreased ecosystem respiration ( R eco ) and gross primary productivity (GPP). As the decrease in R eco was larger than the reduction in GPP, grazing consistently increased the net CO2 sink strength of subtropical pastures (55, 219 and 187 more C/m 2 in 2013, 2014, and 2015). Enteric ruminant fermentation and increased soil wetness due to grazers, increased total net ecosystem CH4 emissions in grazed relative to ungrazed pasture (27–80%). Unlike temperate, arid, and semiarid pastures, where differences in CH4 emissions between grazed and ungrazed pastures are mainly driven by enteric ruminant fermentation, our results showed that the effect of grazing on soil CH4 emissions can be greater than CH4 produced by cattle. Thus, our results suggest that the interactions between grazers and soil hydrology affecting soil CH4 emissions play an important role in determining the environmental impacts of this management practice in a subtropical pasture. Although grazing increased total net ecosystem CH4 emissions and removed aboveground biomass, it increased the net storage of C and decreased the global warming potential associated with C fluxes of pasture by increasing its net CO2 sink strength.